The principle of human dignity in Islamic jurisprudence and its impact on the protection of non-combatants - Rahma, Ahmed Al Domah; Jama'a, Mohammed Hassan; Abdul Majid, Abker Ali; Abdul Rahim, Ahmed Hammad Abdullah (Journal of Economic, Administrative and Legal Sciences, 2018)
The current study dealt with the concept of human dignity in the Islamic jurisprudence and its impact in protecting non-combatants people. The research problem resides in identifying the most important manifestations of human dignity in the Islamic jurisprudence and establishing rules for protection of non-combatants in the Holy Quran, Sunna, the sayings of the companions of Prophet Muhammad, peace be upon Him, and the jurists’ opinions. One of the study’s objectives is to show the principle of human dignity in the Islamic jurisprudence and its most important manifestations in protecting the non-combatants people. An inductive and descriptive methods have been used to conduct the research. The study results showed that the Islamic jurisprudence has the precedence over providing the rules for non-combatants people protection on the basis of human dignity concept. The research has come up with some recommendations, of which the importance of teaching the Islamic jurisprudence, especially the concepts related to human dignity manifestations, methods of combatting and its causes in the academic and military institutions, so as to consolidate the Islamic values and principles.